1985
DOI: 10.1007/bf02023893
|View full text |Cite
|
Sign up to set email alerts
|

Vergleichende Untersuchungen zum Vitamin-B6-Status gravider und nichtgravider Ratten bei unterschiedlicher Vitamin-B6-Versorgung

Abstract: In a two-factorial experiment the influence of graded vitamin B6 supplements on the vitamin B6 status of pregnant and nonpregnant rats was examined. Additionally the question concerning a vitamin B6 super-retention in pregnancy should be investigated. The experiment was carried out with 69 female SPF-Sprague-Dawley rats. Nine rats served as controls and were killed at the beginning of the experiment. On the first experimental day half of the remaining animals were mated at an average body weight of 210 g. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

1989
1989
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
2
9
0
1
Order By: Relevance
“…We rather assumed that especially in carcass neither an excessive accumulation of vitamin B 6 nor a rapid loss of considerable amounts of vitamin B 6 in the case of deficiency occur. This is in agreement with the findings of study of Reithmayer et al (1985a) in which carcass was only poorly affected by various vitamin B 6 supplementations, both in pregnant and growing rats. In pregnant rats, saturation of vitamin B 6 in liver occurred at a dietary vitamin B 6 supplementation of 6 mg/kg (Reithmayer et al, 1986).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…We rather assumed that especially in carcass neither an excessive accumulation of vitamin B 6 nor a rapid loss of considerable amounts of vitamin B 6 in the case of deficiency occur. This is in agreement with the findings of study of Reithmayer et al (1985a) in which carcass was only poorly affected by various vitamin B 6 supplementations, both in pregnant and growing rats. In pregnant rats, saturation of vitamin B 6 in liver occurred at a dietary vitamin B 6 supplementation of 6 mg/kg (Reithmayer et al, 1986).…”
Section: Discussionsupporting
confidence: 94%
“…A dose-response-relationship between the dietary vitamin B 6 intake and the vitamin B 6 status has been determined in several studies with growing, pregnant and lactating rats (Benedikt et al, 1996c, Reithmayer et al, 1985aand b, Roth-Maier and Kirchgeßner, 1981and 1989. However, there are less results to date about the effect of various dietary vitamin B 6 supplies during gestation on the vitamin B 6 level of lactating rats.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…For thiamin, it has been demonstrated that a high supply during pregnancy increases thiamin storage in the body, and therefore the thiamin supply during pregnancy markedly influences both the thiamin status during lactation and the thiamin concentrations in the milk (R oth ‐M aier et al 1990; K irchgessner et al 1997). In contrast, for vitamin B 6 it has been shown that a high supply during pregnancy does not produce additional storage (R eithmayer et al 1985), and therefore vitamin B 6 supply during pregnancy only had a slight influence on the vitamin B 6 status during lactation (R oth ‐M aier et al 1996; B enedikt et al 1996). In order to investigate the physiological behaviour of riboflavin in this respect, rats were fed diets with various supplementary levels of riboflavin during pregnancy and lactation and the concentrations of riboflavin were determined in the liver and carcass after pregnancy and lactation and in the milk of lactating rats.…”
Section: Introductionmentioning
confidence: 99%